Use of inhaled corticoids as a risk factor for community-acquired pneumonia in patients with chronic obstructive pulmonary disease: Uso de corticoides inhalados como factor de riesgo de neumonía adquirida en la comunidad en pacientes con enfermedad pulmonar obstructiva crónica - Castillo Vega, María Alejandra (2023)
Objective: To determine if the use of inhaled corticosteroids is a risk factor for community-acquired pneumonia in patients with Chronic Obstructive Pulmonary Disease at the Víctor Lazarte Echegaray Hospital during the period 2017-2020. Methods: The study was analytical, observational, retrospective of cases and unmatched controls in a ratio of 4:1 with a population of 405 subjects from whom 81 cases and 324 controls were selected, who met the selection criteria. A non-probabilistic sampling was carried out. The variables, use of inhaled corticosteroids, patients with community-acquired pneumonia, age, sex, malnutrition and smoking were included. The association measure was made using Pearson's non-parametric Chi Square test. The bivariate and multivariate analysis was performed using multiple logistic regression with statistical significance (p value <0.05). The study statistician was the Odds ratio (OR). Results: Through the multivariate analysis of the variables under study, no relationship was found between the use of inhaled corticosteroids and patients with community-acquired pneumonia (OR= 1.17; 95%CI: 0.48-2.99 and p value=0.737). It was observed that only age can be considered as a risk factor in view of its significance (OR=1.09; 95%CI: 1.06-1.12 and p value<0.001), while the variables sex, malnutrition, and smoking proved not to be significant ( p> 0.05). Conclusions: The use of inhaled corticosteroids is not a risk factor for community-acquired pneumonia in patients with Chronic Obstructive Pulmonary Disease. Keywords: Chronic Obstructive Pulmonary Disease (COPD), corticosteroids, pneumonia. (source: MeSH NLM)